Os sentidos sociais da penitência transmitidos nas manifestações de grupos culturais do Cariri Cearense - Siqueira, Hermógenes Abraão Paz (2024)
A point of convergence for the meeting of different peoples and customs, Cariri Ceará is a territorial region bordered by Chapada do Araripe and whose main cities are the municipalities of Crato, Juazeiro do Norte and Barbalha. Carrying out this research was based on consideration of its historical trajectory, paying attention to the main milestones of suffering, resistance and festivities that make up its social, cultural and identity formation. Under the general objective of knowing the social meanings of penance transmitted in the manifestations of cultural groups and by penitent masters of the popular culture of Cariri Ceará, the possibility of expanding knowledge of Psychology is related to cultural manifestations, life narratives and memories that are shared by masters who reside in the region. This is research with a qualitative approach and based on studies on the production of meaning in everyday life. Carried out in the municipality of Barbalha, the research included the participation of four masters responsible for the three groups of penitents in the city. As an instrument to analyze the production of data from daily observation and conversation procedures and semi-structured interviews, dialogical maps were used. The religious aspect addressed in the discussion manifests itself not only as a characteristic of the cultural manifestation of groups of penitents, but also as the main element that permeated the experience of the masters and the statements through which they narrate their ways of life. To then understand the processes of initiation into penance and how decurion and masters of their groups were constituted, the analytical articulations carried out were based on the thinking of authors such as Giorgio Agamben, Nego Bispo dos Santos, Walter Benjamin and Michel de Certeau, as well as understanding the evidence of a religious structure sometimes related to Catholicism, sometimes related to capitalism.